INOVASI PEMBELAJARAN PAI DI ERA DIGITAL: STRATEGI MENUMBUHKAN MINAT BELAJAR GEN-Z - Dedi Supriadi; Taufiqurrahman; Samsuddin (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
This research article aims to analyze and explore innovative strategies for Islamic Religious Education (PAI) teaching in the digital era that align with the characteristics of Generation Z. Using a literature review method involving academic sources related to educational technology, gamification, and social media, this study examines the effectiveness of various approaches in PAI learning. The findings indicate that the utilization of Learning Management System (LMS) platforms, quiz-based applications such as Quizizz and Kahoot, as well as the integration of social media platforms like Instagram and TikTok, significantly enhance student engagement. LMS supports flexible learning, gamification boosts motivation, while social media enables creative and relevant content delivery. These results suggest that integrating technology into PAI learning effectively addresses the challenges of the digital era and meets the needs of Generation Z, creating a more dynamic, interactive, and student-centered learning experience